Antisense peptide nucleic acids againstftsZ andefaA genes inhibit growth and biofilm formation of Enterococcusfaecalis. (February 2020) - Narenji, Hanar; Teymournejad, Omid; Rezaee, Mohammad Ahangarzadeh; Taghizadeh, Sepehr; Mehramuz, Bahareh; Aghazadeh, Mohammad; Asgharzadeh, Mohammad; Madhi, Masoumeh; Gholizadeh, Pourya; Ganbarov, Khudaverdi; Yousefi, Mehdi; Pakravan, Asrin; et al.
Abstract: Enterococcus faecalis is one of the important causes of nosocomial infections. Nowadays, increasing prevalence of antibiotic-resistant bacteria and slow progress in recognizing new antimicrobial agents has limited the efficiency of conventional antibiotics, which cause to find novel strategies to overcome bacteria. Therefore, in this study, we aimed to assess the role of efaA gene in the biofilm formation and the role of ftsZ gene in the controlling of bacterial growth by the anti-sense PNAs(Peptide Nucleic Acid). E. faecalis ATCC® 29212™was used for the study of PNAs designed to targeting the start codon section of the ftsZ and efa A genes. PNA attachment to RNA was confirmed by blotting. Electroporation technique was used for the intracellular transfer of anti- ftsZ PNAs. The spot-plating method was used to the assessment of alteration in bacterial growth. Biofilm formation assay and real-time PCR were used for detection of biofilm inhibitory effect of cell penetrating peptide (CPP) conjugated to anti- efaA PNAs.By ftsZ PNAs treatment, no growth was seen from the strain in agar by a spot plating method and the inhibition zone of anti- ftsZ PNAs was not seen. PNAs against the efaA gene decreased by 95% the expression of the efaA gene and biofilm formation. In addition, the(3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide) MTT assay showed no toxicity on MCF7 cells for both of anti- ftsZ and anti- efaA PNAs.This study used new genetic and molecular tools to inhibit pathogenicity and infection by E. faecalis . In this study, we suggested that efaA gene plays a critical role in the biofilm formation and anti- efaA PNAs could decrease the formation of biofilm, as well as, anti- ftsZ PNAs could eliminate bacterial growth. Highlights: PNAs designed against efaA gene was able to reduce biofilm formation. anti- ftsZ was able to inhibit growth of bacteria by interruption in cell division of E. faecalis . efaA gene had an important in biofilm formation of Enterococci spp. PNA can be used as a new advance in control of infection by Enterococci.